PRODUÇÃO DE MUDAS DE KHAYA IVORENSIS NA REGIÃO DE AQUIDAUANA – MS EM SUBSTRATOS DISTINTOS. - Nunes, Irineu Barros; Cardoso Silva, Felipe Mateus; Pereira Alves, Airton Elb; Lima, Edivan Melo; Allegretti Neto, Alberto Renato; Germano Da Silva, Hebert Lizardo (ANAIS DO ENIC, 2018)
-